2010
DOI: 10.1007/s11033-010-0506-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of expressed sequence tag resources for Vanda Mimi Palmer and data mining for EST-SSR

Abstract: Vanda Mimi Palmer (VMP) is a highly sought as fragrant-orchid hybrid in Malaysia. It is economically important in cosmetic and beauty industries and also a famous potted ornamental plant. To date, no work on fragrance-related genes of vandaceous orchids has been reported from other research groups although the analysis of floral fragrance or volatiles have been extensively studied. An expressed sequence tag (EST) resource was developed for VMP principally to mine any potential fragrance-related expressed seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Besides the above mentioned fragrance-related transcripts, no other fragrancerelated cDNAs have been reported from other orchids except Phalaenopsis [20]. We reported here a novel finding of an ACA-like gene from our previously constructed V. Mimi Palmer EST database (VMPEST), designated as VMPACA [4]. The isolated and molecular characterized full-length transcript will allow us to advance our study to understand better the molecular fluxes of terpenoids synthesis in an advanced plant like orchid.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Besides the above mentioned fragrance-related transcripts, no other fragrancerelated cDNAs have been reported from other orchids except Phalaenopsis [20]. We reported here a novel finding of an ACA-like gene from our previously constructed V. Mimi Palmer EST database (VMPEST), designated as VMPACA [4]. The isolated and molecular characterized full-length transcript will allow us to advance our study to understand better the molecular fluxes of terpenoids synthesis in an advanced plant like orchid.…”
Section: Introductionmentioning
confidence: 83%
“…ex G. Don., is a famous ornamental potted plant cultivated in Malaysia selectively for its fragrance characteristic [3,4]. Mohd-Hairul et al [5] found that the floral scent of V. Mimi Palmer was predominated by terpenoid, benzenoid, and phenylpropanoid compounds using GC-MS analyses (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the transcripts were highly expressed in the full-bloom stage, with the sepals and petals having the highest expression levels. Teh et al (2011).…”
Section: Discovery Of Fragrance-related Genes From Vmpestsmentioning
confidence: 99%
“…To date, little information is available regarding the molecular biology of the seed. Analysis of expressed sequence tags (ESTs) is a rapid and effective method to identify novel genes or to investigate gene expression in different tissues, organs and plants [14,15]. Furthermore, EST libraries and databases could provide valuable resources for functional genomic studies [16].…”
Section: Introductionmentioning
confidence: 99%